The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10452-006-9056-0
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Time Series of the Underwater Light Climate in a Shallow Turbid Lake

Abstract: Lake Ü lemiste is a shallow, eutrophic lake which has served the city of Tallinn as a water reservoir for many centuries. Its light climate was studied by combining a routinely measured data set with a modelling approach. For 26 years , data was collected on such optically active substances (OAS) and water parameters as water colour, turbidity and phytoplankton biomass. Simple modelling enabled the quantification of long-term time-series data and the subsequent calculation of the diffuse attenuation coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Also, Reinart & Pedusaar (2008) showed that water colour is a good indicator of the amount of CDOC in the lake.…”
Section: Resultsmentioning
confidence: 98%
“…Also, Reinart & Pedusaar (2008) showed that water colour is a good indicator of the amount of CDOC in the lake.…”
Section: Resultsmentioning
confidence: 98%
“…The euphotic depth, calculated by equation provided by Reinart & Pedusaar (2008) exceeded 2 m, reaching its highest level since 1978, suggested effect of the fish removal. Diatoms, cryptophytes and chrysophytes dominated, restoring some of the seasonality in phytoplankton that used to occur in early 1960s in the lake .…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorus (PO 4 -P) load to the lake decreased from 0.38 g m -2 year -1 in 1991 to 0.18 g m -2 year -1 in 2003. Although the external loading had steadily decreased, there was no constant downward trend in water turbidity (Reinart & Pedusaar, 2008), and cyanobacteria continued to dominate the lake's phytoplankton community (Trei, 2002). The water treatment technology of the plant is adjusted to the water quality in the lake, therefore, better raw water quality, especially in the summer months, would allow more cost-efficient drinking water production.…”
Section: Introductionmentioning
confidence: 98%
“…E z= − In lakes Võrtsjärv and Peipsi, water is typically mixed down to the bottom, therefore mix z was taken equal to the average water depth, avg , Z of the lake (Table 1). For calculating mix E we converted energy units (MJ m -2 day -1 ) into quantum units (mol m -2 day -1 ) according to the relationship 1 J m -2 s -1 = 4.61 µmol m -2 s -1 in air (Reinart et al, 1998;Reinart and Pedusaar, 2008).…”
Section: Determination Of Irradiance Characteristicsmentioning
confidence: 99%
“…In large shallow lakes the influence of resuspended sediment region (PAR, 400-700 nm) is of primary interest. In many limnological studies the diffuse attenuation coefficient over the PAR band d,PAR ( ) K is used to describe the vertical decrease of irradiance in the water column (Paavel et al, 2006(Paavel et al, , 2008Zhang et al, 2007;Reinart and Pedusaar, 2008). If underwater PAR irradiance at different depths is measured, the average d,PAR K for a water column can be estimated using the least square fit of the irradiance vs. depth d,PAR (K is the slope of this exponential regression).…”
mentioning
confidence: 99%